Goos-Hänchen Lateral Displacements at the Interface between Isotropic and Gyroelectric Media - Jinbao Wang; Hui Huang; Cheng Chen; Hanfeng He; Yuanyuan Dong; Huan Qi (International Journal of Antennas and Propagation)
A detailed study on Goos-Hänchen (GH) lateral displacements of the reflected and transmitted waves propagating at the interface between an isotropic medium and a gyroelectric medium in Voigt configuration is presented. After the reflection coefficient and transmission coefficient are derived, based on the stationary phase approach, GH lateral displacements are obtained analytically. The numerical results for a specific gyroelectric medium are also given. It shows that with the existence of an applied magnetic field, the GH effect occurs not only during total reflection but also during nontotal reflection, which is not true for isotropic media. Moreover, due to the nonreciprocal property of the gyroelectric medium, the sign of the incident angle also influences the displacements. Finite-element method simulations have verified the theoretical results.